Masculinities and suicide: A systematic review and meta-analysis - Charlotte Starkey; Fhionna Moore (PLoS ONE, 2026)
Background Women are more likely to report suicidal ideation and make suicide attempts, while men are more likely to die by suicide. There has been much discussion of the possible contribution of masculinity (i.e., attitudes, beliefs, and behaviours understood to be ‘masculine’ through construction of gendered identities in local contexts) to this gender paradox of suicide. Here we report the first systematic literature review, meta-analysis, and meta-regression testing relationships between measures of masculinity and suicidality. Methods We searched for articles using the following search terms in Google Scholar, Web of Science, PubMed, and APA PsychINFO in July 2024 ((“gender role*” OR “gender-role*” OR “sex role*” OR “sex-role*” OR “masculin*” (TOPIC)) AND (“suicid*” (TOPIC))). We excluded papers which examined non-suicidal self-injury, were not based on individual-level valid and reliable quantitative measures of masculinity and suicidality, and which did not provide sufficient statistical information to compute effect size. Results Across 23 studies the relationship between the multiple and diverse measures of masculinity and of suicidality overall was non-significant (r = 0·03 [95% CI: −0·01, 0·1], z = 1.75, p = 0.341) and showed significant heterogeneity. Given the range of operationalisations of masculinity included, and the high heterogeneity, we urge caution in interpreting the pooled overall relationship. Meta-regression showed moderation of the overall relationship by both measure of masculinity and suicidality. That is, the positive relationship between masculinity and suicidality was stronger for measures of masculinity that focussed on emotional restriction and pursuit of status, and for suicidal action than ideation. Conversely, there were inverse relationships between strength-based measures of masculinity and suicidality. Limitations Our results demonstrated significant heterogeneity, and measures of masculinity are likely to be largely outdated. Conclusions Our results suggest there is value in further work identifying specific aspects of contemporary psychological masculinity which link to suicidality, which is of relevance to clinical assessment and management of suicidality.